The Chinese longsnout catfish genome provides novel insights into the feeding preference and corresponding metabolic strategy of carnivores - Liu, Yulong; Zhai, Gang; Su, Jingzhi; Gong, Yulong; Yang, Bingyuan; Lu, Qisheng; Xi, Longwei; Zheng, Yutong; Cao, Jingyue; Liu, Haokun; Jin, Junyan; Zhang, Zhimin; et al. (Genome Research, 2024)
Fish show variation in feeding habits to adapt to complex environments. However, the genetic basis of feeding preference and the corresponding metabolic strategies that differentiate feeding habits remain elusive. Here, by comparing the whole genome of a typical carnivorous fish (Leiocassis longirostris Günther) with that of herbivorous fish, we identify 250 genes through both positive selection and rapid evolution, including taste receptor taste receptor type 1 member 3 (tas1r3) and trypsin. We demonstrate that tas1r3 is required for carnivore preference in tas1r3-deficient zebrafish and in a diet-shifted grass carp model. We confirm that trypsin correlates with the metabolic strategies of fish with distinct feeding habits. Furthermore, marked alterations in trypsin activity and metabolic profiles are accompanied by a transition of feeding preference in tas1r3-deficient zebrafish and diet-shifted grass carp. Our results reveal a conserved adaptation between feeding preference and corresponding metabolic strategies in fish, and provide novel insights into the adaptation of feeding habits over the evolution course.
10.1101/gr.278476.123